Chipless RFID for space applications - Moscato, Stefano; Moro, Riccardo; Bozzi, Maurizio; Perregrini, Luca; Sakouhi, Soumaya; Dhawadi, Fatma; Gharsallah, Ali; Savazzi, Pietro; Vizziello, Anna; Gamba, Paolo (2014 IEEE International Conference on Wireless for Space and Extreme Environments (WiSEE), 2014)
Recent works reveal a great deal of interest in the subject of wireless passive sensor for space applications. In particular, wireless passive tags can be employed during in-flight operations as well as during ground test campaigns, thanks to their robustness in extreme environments since they do not contain batteries nor any active electronic circuits. Chipless backscatter-based radio frequency identification (RFID) could be a valid alternative to surface acoustic wave (SAW) imple-mentations, especially for short-range applications like sensor monitoring aboard of satellite systems. In this work we present chipless RFIDs based on resonant substrate integrated waveguide (SIW) cavities, showing both the experimental characterization and system simulations, proving the solution feasibility for their usage on space platforms.